Variations in motility and biofilm formation of salmonella enterica serovar typhi gut pathogens - Chelvam, Kalaivani Kalai; Chai, L.C.; Thong, Kwai Lin (BMC, 2014)
Background: Salmonella enterica serovar Typhi (S. Typhi) exhibits unique characteristics as an intracellular human pathogen. It causes both acute and chronic infection with various disease manifestations in the human host only. The principal factors underlying the unique lifestyle of motility and biofilm forming ability of S. Typhi remain largely unknown. The main objective of this study was to explore and investigate the motility and biofilm forming behaviour among S. Typhi strains of diverse background. Results: Swim and swarm motility tests were performed with 0.25% and 0.5% agar concentration, respectively; while biofilm formation was determined by growing the bacterial cultures for 48 hrs in 96-well microtitre plate. While all S. Typhi strains demonstrated swarming motility with smooth featureless morphology, 58 out of 60 strains demonstrated swimming motility with featureless or bull’s eye morphology. Interestingly, S. Typhi strains of blood-borne origin exhibited significantly higher swimming motility (P < 0.05) than stool-borne strains suggesting that swimming motility may play a role in the systemic invasion of S. Typhi in the human host. Also, stool-borne S. Typhi displayed a negative relationship between motility and biofilm forming behaviour, which was not observed in the blood-borne strains. Conclusion: In summary, both swimming and swarming motility are conserved among S. Typhi strains but there was variation for biofilm forming ability. There was no difference observed in this phenotype for S. Typhi strains from diverse background. These findings serve as caveats for future studies to understand the lifestyle and transmission of this pathogen. Keywords: Salmonella Typhi, Biofilm, Motility swarming, Swimming